2015
DOI: 10.1016/j.econmod.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting macroeconomic data for an emerging market with a nonlinear DSGE model

Abstract: This paper considers the forecasting performance of a nonlinear dynamic stochastic general equilibrium (DSGE) model. The results are compared to a wide selection of competing models, which include a linear DSGE model and a variety of vector autoregressive (VAR) models. The parameters in the VAR models are estimated with classical and Bayesian techniques; where some of the Bayesian models are augmented with stochastic-variable-selection, time-varying parameters, endogenous structural breaks and various forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In a few studies, small-scale nonlinear DSGE models are estimated (Pichler, 2008; Gust et al, 2012; Fernandez-Villaverde et al, 2010). Most of them use only three observed variables: output, the nominal interest rate and inflation (Amisano and Tristani, 2010; Pichler, 2008;Balcilar et al, 2014;Gust et al, 2012). A few studies use other observed variables: Doh (2011) uses additional data about the yield curve, while, Hall (2012) uses consumption instead of output.…”
Section: Introductionmentioning
confidence: 99%
“…In a few studies, small-scale nonlinear DSGE models are estimated (Pichler, 2008; Gust et al, 2012; Fernandez-Villaverde et al, 2010). Most of them use only three observed variables: output, the nominal interest rate and inflation (Amisano and Tristani, 2010; Pichler, 2008;Balcilar et al, 2014;Gust et al, 2012). A few studies use other observed variables: Doh (2011) uses additional data about the yield curve, while, Hall (2012) uses consumption instead of output.…”
Section: Introductionmentioning
confidence: 99%
“…These studies develop more sophisticated frameworks that allow for various real and nominal rigidities in closed and small open economy NKDSGE models for South Africa and find that DSGEbased inflation forecasts tend to outperform those obtained from BVAR and VAR models. In addition, Balcilar et al (2013) show that by including non-linearities in the DSGE framework to account for structural changes in South Africa's economy, Non-linear DSGE-based forecasts outperform those from the linear counterpart, as well as VAR models. In the same breadth, other studies (e.g.…”
Section: Ex-ante Forecasting Of Inflation Variablesmentioning
confidence: 98%
“…Overall, the preferred choice is the specification with λ = 1. On the other hand, RMSE statistics associated with the auxiliary 7 In addition to comparing the DSGE model's performance in forecasting core variables to that of the benchmark autoregressive AR(1) model, we also considered the forecast performance of the Vector Autoregressive (VAR), Bayesian VAR (BVAR) models as well as forecast combination based on the simple mean of the forecasts from the AR, VAR and BVAR, all estimated with one lag. On the whole (for h = 2, h = 4 and h = 12), we find that DSGE-based forecasts for the inflation variable are still associated with smallest forecast errors compared to the other benchmarks.…”
Section: Forecasting Of Non-core Variablesmentioning
confidence: 99%
“…Gupta and Kabundi (2010;2011) investigate large-scale Factor Models (FMs) for forecast performance, while Ngoie and Zellner (2012) illustrate the forecasting power of a disaggregated Marshallian macroeconomic model. DSGE models used for forecasting include various closed-economy Dynamic Stochastic General Equilibrium (DSGE) models (Liu & Gupta, 2007;Liu, Gupta & Schaling, 2009;, small open economy New Keynesian DSGE models (Steinbach, Mathuloe & Smit, 2009;Alpanda, Kotzé & Woglom, 2011), small open economy New Keynesian DSGE-VAR model (Gupta & Steinbach, 2013) and a recent closedeconomy nonlinear DSGE model (Balcilar, Gupta & Kotzé, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%